Sistemic Review and Meta-Analysis: PCR For Early Detection Of Infection Intrauterine And Prediction Obstetric Complications In High-Risk Pregnancy - Evi Irianti; Siregar, Ice Ratnalela (Jurnal Teknokes, 2025)
Intrauterine infection is a major cause obstetric complications, including preterm birth, premature rupture of membranes (PROM), and low birth weight (LBW). Polymerase Chain Reaction (PCR) testing offers rapid and sensitive molecular detection compared to conventional diagnostic methods. This study is a systematic review and meta analysis conducted following the PRISMA 2020 guidelines, aimed at evaluating the effectiveness of PCR in detecting intrauterine infection and predicting performed using PubMed, Scopus, ScienceDirect, Wiley and SpringerLink (2020 - 2025). The pooled analysis demonstrated a sensitivity of 0.90, specificity of 0,93 and an Area Under the Curve (AUC) of 0,95 with a Diagnostic Odds Ratio (DOR) of approximately 120. Postive PCR results were significantly associated with an increased risk of preterm birth (OR 3,4), LBW (OR 2,8) and PROM (OR 2,2). PCR demonstrated high diagnostic accuracy and strong prognostic value, supporting its integration into risk based antenatal screening to reduce perinatal morbidity and mortality.